FACTORS AFFECTING REVISIT INTENTION THROUGH CUSTOMER SATISFACTION IN THEME PARK - Lalita Sekar Ryani; Harry Soesanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Amusement parks are also considered to be a promising industry in Indonesia due to the growing economy and middle class population that has grown in recent years. Competition in the rides industry is increasing in line with the popularity of this destination. Industry players are competing to create value or privilege among the many rides to play in Indonesia. One of the things that is important to note is how players in the playground industry can focus on consumers so that the playground business can be sustainable.This study aims to determine physical attributes, interactions with customers, interactions with employees, customer satisfaction and interest in returning to visit. The data source used in this research is primary data, The technique chosen to support research activities related to sampling in this research is the Nonprobability Sampling technique with accidental sampling. This research make use of Structural Equation Modeling (SEM) as a statistical instrument in an effort to test various hypotheses that have been determinedwith the help of SEM. The results showed thatPhysical attributes have a positive effect on customer satisfaction; Physical attributes have a positive effect on interest in returning to visit; Interaction with customers has a positive effect on customer satisfaction; Interaction with customers has a positive effect on interest in returning to visit; Interaction with employees has a positive effect on customer satisfaction; Interaction with customers has a positive effect on interest in returning to visit; customer satisfaction has a positive effect on interest in returning to visit Keywords: Physical Attributes; Interaction with Customers; Interaction with Employees; Customer satisfaction; Returning Interest; Playground; SEM